The effects of celery leave extract on male hormones in rats - Kooti Wesam; Ghasemi-boroon Maryam; Ghafourian Mehri; Asadi-Samani Majid; Harizi Mahmoud; Sharafi-Ahvazi Naim; Afrisham Reza (Shahrekord University of Medical Sciences, 2015)
Introduction: Celery (Apium graveolens) belongs to the Umbelliferae family, and has a plenty of nutritional and pharmaceutical applications. The presence of phytoestrogenic compounds has been reported in this plant. These compounds may affect the pituitary-gonad axis. The aim of the present study was to evaluate the efficacy of hydro-alcoholic extracts of celery leaves on serum levels of testosterone, LH and FSH in male rats. Methods: In this experimental study, 32 male Wistar rats were divided into four groups, eight rats included in each. The control group did not receive any treatment. The placebo group received distilled water and the case groups received 200 and 300 mg/kg/B.W of hydro-alcoholic celery leaf extract for 20 consecutive days by oral administration. After completion of the treatment, the rats were anesthetized and blood sampling from their heart was carried out. Then, serum levels of testosterone, LH and FSH were measured using immunoassay methods. The obtained data were analyzed by the SPSS using the statistical ANOVA test. Results: The level of LH in the case group receiving 200 mg/kg B.W of celery extract showed a significant decrease compared with the control and placebo groups (P<0.05). The level of FSH and testosterone in case groups did not show any significant difference in comparison with the control group (P>0.05). Conclusion: The result of the present study shows that in the administered dose, celery extract does not have any considerable side effect on the secretion of hormones in male rats.